2021
DOI: 10.3390/su13126973
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Emotions When Using E-Portfolios in Virtual Education Environments

Abstract: This paper is based on a study that aims to understand the emotions students feel when they use the e-portfolio to manage their learning and assessment. The sample was composed of 358 students, and the instrument used was an ad hoc questionnaire. The students were asked to indicate the degree to which they experienced a set of emotions when using the e-portfolio. From the results obtained, it can be concluded that positive emotions are foremost and above average, ranked as follows from strongest to weakest: fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Classifications and taxonomies of emotions can be found in the literature. 11 – 17 Attempts have been made to establish classifications of basic emotions; however, there is still no one generally accepted categorization 12 . It is important to remember that emotional reaction improves rather than suppresses learning results.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Classifications and taxonomies of emotions can be found in the literature. 11 – 17 Attempts have been made to establish classifications of basic emotions; however, there is still no one generally accepted categorization 12 . It is important to remember that emotional reaction improves rather than suppresses learning results.…”
Section: Introductionmentioning
confidence: 99%
“…Students in teacher education programs indicated that they felt more curiosity and inquiry than students in other academic programs. 12 In addition, when comparing students at the beginning or end of their academic track, senior students experienced more positive feelings, such as freedom, curiosity, and inquiry, related to ICT usage, than newer students. Newer students described more negative feelings, such as disorientation and a waste of time when using ICT than senior students.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations